"Learning to become a better man": Insights from a fathering programme for incarcerated Indigenous men. Issue 1 (March 2017) - Rossiter, Chris; Power, Tamara; Fowler, Cathrine; Jackson, Debra; Roche, Michael; Dawson, Angela
Abstract: This paper reports a qualitative study of incarcerated Indigenous fathers in Australia, using a framework of generative fathering. Researchers interviewed 28 imprisoned Indigenous men about their experiences of parenting and their responses to a parenting programme. Participants identified how the programme supported their learning and their capacity to embrace the role of parenting the next generation. Responses indicate that the programme's format and content were relevant to their experience as Indigenous fathers, and enhanced by the skills of the facilitator, and provision of a safe learning environment. It facilitated their growth as individuals and as parents through acknowledging their cultural identity and roles.